The Relationship Between Blood Sugar And Severity Of Diabetic Retinopathy In Type 2 Diabetes Mellitus Patients - Ainunnisa Muhammad; Ratih Nastasha Maharani; Andi Oddang (Jurnal EduHealth, 2024)
DM will trigger the emergence of complications, both macrovascular and microvascular. Diabetic retinopathy is one of the most common eye complications in diabetes mellitus patients. The research was carried out by collecting secondary data from various research journal sources for 2020-2024. The results of the study show that there is a relationship between blood sugar and the severity of diabetic retinopathy in type 2 Diabetes Mellitus patients, so by controlling glycemia, namely HbA1c, it can prevent the severity of diabetic retinopathy.